Advance routing strategy for VANETs. Issue 4 (11th November 2021) - Suman, Amrit; Kumar, Chiranjeev; Suman, Preetam
Intelligent transportation in VANET helps increase transportation efficiency, enhance safety in traffic, and improve the driving experience. In this paper, a routing strategy is proposed based on AODV and MAC to enhance the route discovery and avoid collision. The proposed routing strategy consists of automatic size adjustment of contention window depending on the network capacity, channel allocation for each node, priority assigning for different types of messages, and security checking for each packet using CRC; all these are based on MAC. Route discovery and table preparation are based on the AODV. The proposed routing protocol (P-Routing) has been implemented in Qualnet 5.0. The results with the performance of C-AODV were then compared with existing protocols with various parameters. In all cases, the performance of the proposed protocol is better. The results are described with the graphs in the result section.